The ecophysiological performance of Vernonia polyanthes Less. (Asteraceae) in conserved and degraded forests in the Brazilian Cerrado - Baron, Daniel [UNESP]; Graciano, Diego da Silva [UNESP]; Portella, Roberto de Oliveira [UNESP]; Benetti Mantoan, Luis Paulo [UNESP]; Rolim de Almeida, Luiz Fernando [UNESP]; Fernandes Boaro, Carmen Silvia [UNESP] (Springer, 2015)
This study was performed to determine whether the environmental conditions of the Cerrado domain could directly influence photosynthesis (primary metabolism) and essential oil production (secondary metabolism) in adult Vernonia polyanthes Less. plants. In the experiments of this investigation, which were conducted in two areas of the Cerrado (conserved and degraded) during the dry season (winter), leaf CO2 assimilation rate, transpiration, stomatal conductance, instantaneous carboxylation efficiency, leaf water potential, soil potential and essential oil yield were evaluated. V. polyanthes plants exhibited outstanding growth in the conserved forests of the Brazilian Cerrado, with a higher leaf CO2 assimilation rate, instantaneous carboxylation efficiency, leaf water potential, soil potential and essential oil yield than in degraded regions of the Cerrado. Interestingly, the Cerrado sensu stricto was associated with lower performance with respect to essential oil yield and transpiration but no alteration of stomatal conductance, an essential determinant of gas exchange parameters. Our data suggest that ecophysiological effects in conserved and degraded areas in the Cerrado modify gas exchange and essential oil production in V. polyanthes.
Keywords: Asteraceae; Gas exchange; Water relations; Specialized metabolism; Cerrado